The conservation of natural resources a series of lectures delivered at the Institution. (Institution of Civil Engineers, 1957)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. A series of lectures delivered at the ICE May 1955-Dec 1956.